Firewood heat electrification impacts in the Chilean power system. (September 2020) - Verástegui, Felipe; Lorca, Álvaro; Negrete-Pincetic, Matias; Olivares, Daniel
Abstract: Chile presents an extended use of low-quality firewood for residential heating. This raises serious concerns, mainly related to health problems due to particulate emissions from firewood combustion. Several initiatives have been considered by the Chilean government to address this, including heat electrification goals. In addition, the Chilean power system is undergoing a decarbonization process. This paper analyzes the impacts of firewood heat electrification over the Chilean power system's decarbonization process until 2044, based on a capacity expansion planning model and an estimation of firewood heat demand, to account for major changes in load shape and spatial distribution. The results show that there is a large increase in the power system total cost (ranging from 5.6% to 19.4%), with flexibility requirements becoming larger in the south. Technologies that strongly depend on local resource availability, such as wind and concentrated solar power, present changes in their systemic value, altering the need for storage and flexibility. Also, aspects such as household insulation, electrification efficiency, and smart heating technologies would significantly impact the process in terms of cost reduction and optimal generation mix. The policy implications for the Chilean power system are presented, within the broader discussion of the overall firewood problem. Highlights: Heat electrification and decarbonization may have a large impact on the power system. Expansion planning models provide a valuable framework for assessing these processes. Flexibility requirements largely increase under heat electrification in Chile. Effective balance of renewable and flexible sources is key for sustainability.